2015 International Conference on Cloud Computing (ICCC) 2015
DOI: 10.1109/cloudcomp.2015.7149632
|View full text |Cite
|
Sign up to set email alerts
|

Arabic Text Mining a Systematic Review of the Published Literature 2002-2014

Abstract: Text Mining is a set of techniques that analyzes large masses of data, extract relations that are unknown beforehand, and provide solutions to help decision-making. Text mining had been used extensively to analyze English text. However, text mining has only been used recently in analyzing Arabic text. As a result the objective of this paper is to present the current state of Arabic text mining. A systematic review has been performed to collect the papers published on the analysis of Arabic text mining. More th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 91 publications
0
7
0
1
Order By: Relevance
“…The scholars of Shariah have a central role to play that shapes a bank's operations according to the laws and principles of Islam (MohdThasThaker et al, 2018). By appointing an internal Shariah audit, the SSB can exert pressure on the branches of a particular bank (Al-Mahmoud, 2007). An SSB must ensure that bank's branches fulfill all its obligations toward their stakeholders' concern, as mentioned in Islam's law (Maali et al, 2006;Farook et al, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The scholars of Shariah have a central role to play that shapes a bank's operations according to the laws and principles of Islam (MohdThasThaker et al, 2018). By appointing an internal Shariah audit, the SSB can exert pressure on the branches of a particular bank (Al-Mahmoud, 2007). An SSB must ensure that bank's branches fulfill all its obligations toward their stakeholders' concern, as mentioned in Islam's law (Maali et al, 2006;Farook et al, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The authors highlighted the proposed solutions of mining problems, and also identified the remaining unsolved issues and new challenges. In [10], a systematic literature review is conducted to analyze the current state of Arabic text mining. For this review, more than one hundred papers are selected from different reliable sources and then were classified according to their specific domains.…”
Section: Related Workmentioning
confidence: 99%
“…As previously mentioned, the aim of this study is to investigate event-based surveillance systems that can process Arabic texts in the domain of disease outbreaks. Al-Mahmoud and Al-Razgan [23] conducted a systematic review of published works on Arabic text mining between 2002 and 2014. The review showed that the topics of the articles were limited to a few different domains, such as opinion mining, crime domain, social networks, Arabic Wikipedia, and Islamic studies.…”
Section: Disease Outbreak Surveillance Systems In Arabicmentioning
confidence: 99%